Treatment of Recurrent Primary Cutaneous Mucinous Carcinoma of the Eyelid with Modified Wide Local Excision - Stephanie M. Tillit; Siva S. R. Iyer; Eric J. Grieser; John T. LiVecchi (Case Reports in Ophthalmological Medicine)
Primary cutaneous mucinous carcinoma (PCMC) is a rare, low-grade malignant neoplasm of the sweat gland, whose history has been controversial regarding eccrine versus apocrine origin. This case report describes a 53-year-old male who presented to the University of Florida, Gainesville, ophthalmology clinic and was referred to the oculoplastics service with a painless, subcentimeter mass on the lateral right upper eyelid including the canthus, consistent with recurrent primary cutaneous mucinous carcinoma of the eyelid. Four years prior, the patient had undergone excisional biopsy of the lesion in a clinic, which revealed residual tumor, but the patient deferred further surgery at the time. The patient underwent surgical excision of the mass with reconstruction without operative complications and with negative surgical margins. PCMC is difficult to diagnose clinically due to its rarity and requires a histopathological examination for confirmation of the diagnosis. This report presents the first case in the literature of primary cutaneous mucinous carcinoma in a patient with human immunodeficiency virus (HIV). With this case report, we aim to raise awareness of primary cutaneous mucinous carcinoma as a potential part of the differential diagnosis for malignant eyelid lesions, including those present in patients with HIV.